Enhanced Ionic and Electronic Conductivity of Polyacetylene with Dendritic 1, 2, 3‐Triazolium‐Oligo(ethylene glycol) Pendants. Issue 11 (26th April 2018) - Wang, Cuifang; Li, Hongfei; Zhang, Hengchen; Sun, Ruyi; Song, Wei; Xie, Meiran
Abstract: The ionic polyacetylenes (iPAs) with dendritic 1, 2, 3‐triazolium‐containing oligo(ethylene glycol) (OEG) pendants are prepared by metathesis cyclopolymerization. The dendritic triazolium and flexible OEG pendants endow the iPAs with low glass transition temperature of −29.0 °C and enhanced intrinsic ionic conductivity (σi ) of 5.0 × 10 −5 S cm −1 at 30 °C under anhydrous conditions. After solution doping with bis(trifluoromethane)sulfonimide lithium (LiTFSI), the σi of iPAs reaches up to 5.2 × 10 −4 S cm −1 . When doped with iodine (I2 ), the iPAs exhibit high electronic conductivity (σe ) of 1.3 × 10 −5 S cm −1 . If doped with both LiTFSI and I2, the iPAs demonstrate the best dual σi and σe of 8.3 × 10 −4 and 1.2 × 10 −5 S cm −1, respectively. Therefore, the dendritic triazolium‐OEG pendants‐functionalized iPAs display an improved conductive performance compared with the corresponding iPAs bearing dendritic triazolium‐alkyl pendants, or branched triazolium‐OEG pendants, before and after doping with different dopants, and will have the potential applications in electronics as the dual conductive materials. Abstract : Ionic polyacetylenes with flexible dendritic 1, 2, 3‐triazolium‐oligo(ethylene glycol) pendants are synthesized by metathesis cyclopolymerization. The ionic conductivity of polyacetylenes is 5.0 × 10 −5 S cm −1 and achieves 8.3 × 10 −4 S cm −1 combined with a simultaneous electronic conductivity of 1.2 × 10 −5 S cm −1 after doping with bis(trifluoromethane)sulfonimide lithium and iodine, which is enhanced compared with those of corresponding polyacetylenes bearing dendritic or branched triazolium‐alkyl pendants.